Inclusive practices in teacher training in Mexico - Flores Barrera, Vasthi Jocabed (2017)
Inclusive practices include diversity as a resource that favors teaching-learning processes in the classroom, although they focus on the most vulnerable people by offering them higher-quality education. This descriptive study sought to identify the inclusive practices of teachers who train teachers in an Escuela Normal (teachers’ college) in Mexico. Eight teachers and 247 students participated in the study; the Guidelines for the Evaluation of Inclusive Practices in the Classroom (observation formats and students), the Learning Strategies Questionnaire, and semi-structured interviews were used. The results suggest that, although the general perception is that participating teachers have high inclusive practices, they need greater support in the physical conditions of the classroom, methodology and teacher-student relationship. It was also identified the need for a refresher program for teachers to conceptually enrich the teaching staff and encourage the implementation of inclusive education within the Escuela Normal.  DOI: https://doi.org/10.24265/liberabit.2017.v23n1.03